Lipid Droplets: A New Player in Colorectal Cancer Stem Cells Unveiled by Spectroscopic Imaging. (18th December 2014) - Tirinato, Luca; Liberale, Carlo; Di Franco, Simone; Candeloro, Patrizio; Benfante, Antonina; La Rocca, Rosanna; Potze, Lisette; Marotta, Roberto; Ruffilli, Roberta; Rajamanickam, Vijayakumar P.; Malerba, Mario; De Angelis, Francesco; et al.
Abstract: The cancer stem cell (CSC) model is describing tumors as a hierarchical organized system and CSCs are suggested to be responsible for cancer recurrence after therapy. The identification of specific markers of CSCs is therefore of paramount importance. Here, we show that high levels of lipid droplets (LDs) are a distinctive mark of CSCs in colorectal (CR) cancer. This increased lipid content was clearly revealed by label-free Raman spectroscopy and it directly correlates with well-accepted CR-CSC markers as CD133 and Wnt pathway activity. By xenotransplantation experiments, we have finally demonstrated that CR-CSCs overexpressing LDs retain most tumorigenic potential. A relevant conceptual advance in this work is the demonstration that a cellular organelle, the LD, is a signature of CSCs, in addition to molecular markers. A further functional characterization of LDs could lead soon to design new target therapies against CR-CSCs. Stem Cells 2015;33:35–44